Annexin A1 based inflammation resolving mediators and nanomedicines for inflammatory bowel disease therapy. (November 2022) - Xu, Runxin; Weber, Marie-Christin; Hu, Xinkai; Neumann, Philipp-Alexander; Kamaly, Nazila
Abstract: Inflammatory bowel diseases (IBD) such as Crohn's Disease (CD) and Ulcerative Colitis (UC) are chronic, progressive, and relapsing disorders of the gastrointestinal tract (GIT), characterised by intestinal epithelial injury and inflammation. Current research shows that in addition to traditional anti-inflammatory therapy, resolution of inflammation and repair of the epithelial barrier are key biological requirements in combating IBD. Resolution mediators include endogenous lipids that are generated during inflammation, e.g., lipoxins, resolvins, protectins, maresins; and proteins such as Annexin A1 (ANXA1). Nanoparticles can specifically deliver these potent inflammation resolving mediators in a spatiotemporal manner to IBD lesions, effectively resolve inflammation, and promote a return to homoeostasis with minimal collateral damage. We discuss these exciting and timely concepts in this review.